Unlocking science : morphology in the intermediate years : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Teaching and Learning at Massey University, Aotearoa New Zealand - Harwood, Lisa Wendy (Massey University, 2025)
This study investigates how intermediate teachers in Aotearoa New Zealand currently teach scientific texts and their understanding of morphology as a strategy to support vocabulary acquisition. Morphological awareness, the ability to consciously analyse and use meaningful word parts, has been linked to vocabulary growth and comprehension. However, its role in science instruction remains underexplored. To gain an understanding of this problem, semi-structured interviews with four intermediate and science teachers were analysed using reflexive thematic analysis. The five themes that emerged include the following: 1. Gaps in discipline-specific vocabulary limit students’ ability to express scientific understanding 2. Science vocabulary instruction is informal, variable, and lacks system-wide consistency 3. Teachers show limited understanding of morphology and use it only incidentally 4. Teachers want practical, science-aligned morphology instruction with clear examples and support 5. Structural constraints and disciplinary perceptions limit literacy integration in science. Findings indicate that while participants value vocabulary instruction to support comprehension, they lack systematic strategies to embed morphology into their classroom instruction. Drawing on analysis of participant interviews and existing research, a framework is proposed that integrates student routines and teacher professional development to reduce cognitive barriers and promote equitable access to the language of science. This study demonstrates how morphology can be embedded to strengthen both literacy and science learning within Aotearoa New Zealand’s intermediate-level classrooms.
Keywords: 390113 Science, technology and engineering curriculum and pedagogy; 390304 Primary education